N‐homocysteinylation of tau and MAP1 is increased in autopsy specimens of Alzheimer's disease and vascular dementia. Issue 3 (19th March 2019) - Bossenmeyer‐Pourié, Carine; Smith, A David; Lehmann, Sylvain; Deramecourt, Vincent; Sablonnière, Bernard; Camadro, Jean‐Michel; Pourié, Grégory; Kerek, Racha; Helle, Deborah; Umoret, Remy; Guéant‐Rodriguez, Rosa‐Maria; Rigau, Valérie; et al.
Abstract: The pathomechanisms that associate a deficit in folate and/or vitamin B12 and the subsequent hyperhomocysteinemia with pathological brain ageing are unclear. We investigated the homocysteinylation of microtubule‐associated proteins (MAPs) in brains of patients with Alzheimer's disease or vascular dementia, and in rats depleted in folate and vitamin B12, Cd320 KO mice with selective B12 brain deficiency and H19‐7 neuroprogenitors lacking folate. Compared with controls, N‐homocysteinylated tau and MAP1 were increased and accumulated in protein aggregates and tangles in the cortex, hippocampus and cerebellum of patients and animals. N‐homocysteinylation dissociated tau and MAPs from β‐tubulin, and MS analysis showed that it targets lysine residues critical for their binding to β‐tubulin. N‐homocysteinylation increased in rats exposed to vitamin B12 and folate deficit during gestation and lactation and remained significantly higher when they became 450 days‐old, despite returning to normal diet at weaning, compared with controls. It was correlated with plasma homocysteine (Hcy) and brain expression of methionine tRNAsynthetase (MARS), the enzyme required for the synthesis of Hcy–thiolactone, the substrate of N‐homocysteinylation. Experimental inactivation of MARS prevented the N‐homocysteinylation of tau and MAP1, and the dissociation of tau and MAP1 from β‐tubulin and PSD95 in cultured neuroprogenitors. In conclusion, increased N‐homocysteinylation of tau and MAP1 is a mechanism of brain ageing that depends on Hcy concentration and expression of MARS enzyme. Its irreversibility and cumulative occurrence throughout life may explain why B12 and folate supplementation of the elderly has limited effects, if any, to prevent pathological brain ageing and cognitive decline. Copyright © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.